Relationship marketing of professional services by international accounting firms in South Africa - Röhrs, Rainer Georg (My University, 2011)
The international accounting firms in South Africa are placing significant emphasis on relationship marketing of their professional services divisions. The reason for this is that internationally and locally, significant restrictions have been imposed on auditing firms, in providing professional services to their audit clients, which is as a result of a number of corporate failures in recent years. The objective of this research was to determine whether the relationship marketing performance criteria exercised by the largest four international accounting firms in South Africa are in accordance with client’s importance perceptions. The research methodology employed consisted of two stages. The first part of the research focused on a comprehensive literature review. The literature review was undertaken to determine what characteristics distinguish services marketing from traditional product marketing as well as what attributes contribute towards successful relationship marketing. Thereafter, in-depth interviews were conducted to understand customer perceptions of the effectiveness of relationship marketing of the international accounting firms, as well as to identify any additional attributes which they considered important. A convenience sample of 16 interviewees was selected and consisted of customers who had previously purchased professional services from the international accounting firms. The results of the interviews conducted were analysed. The study revealed that the professional services relationship marketing employed by the international accounting firms were in line with customer expectations. However, there is room for further improvement as not all customers are seeking the same type of relationship with their service providers with each relationship having to be managed differently. The study also identified attributes which were not highlighted during the literature review undertaken. To help the international accounting firms improve the effectiveness of their relationship marketing initiatives, the study includes recommendations on the different form which such practices should incorporate.
MBA - WBS
Keywords: Relationship marketing; Accounting firms; Auditors